Effect of biofilter on the environmental parameters and growth of goldfish (Carassius auratus) - Ahilan, B; Jayaseelan, M J Prince (Indian Journal of Fisheries, 2011)
The investigation was aimed at determining the effect of biofilter on the environmental parameters and growth of goldfish. The goldfish were reared in the flowthrough circular cement cisterns connected with biofilter unit and without biofilter. The important environmental parameters were estimated for a period of two months. The water pH and DO levels showed diurnal variation. The mean gross fish production was higher in the tank fitted with biofilter ( 291g /5m3)than the tank without biofilter ( 260g / 5m3).